Role of post-translational modifications of Sp1 in cardiovascular diseases - Sun, Xutao; Zhou, Qi; Xiao, Chengpu; Mao, Caiyun; Liu, Ying; Chen, Guozhen; Song, Yunjia (Frontiers in Cell and Developmental Biology, 2024)
Specific protein 1 (Sp1) is pivotal in sustaining baseline transcription as well as modulating cell signaling pathways and transcription factors activity. Through interactions with various proteins, especially transcription factors, Sp1 controls the expression of target genes, influencing numerous biological processes. Numerous studies have confirmed Sp1's significant regulatory role in the pathogenesis of cardiovascular disorders. Post-translational modifications (PTMs) of Sp1, such as phosphorylation, ubiquitination, acetylation, glycosylation, SUMOylation, and S-sulfhydration, can enhance or modify its transcriptional activity and DNA-binding stability. These modifications also regulate Sp1 expression across different cell types. Sp1 is crucial in regulating non-coding gene expression and the activity of proteins in response to pathophysiological stimuli. Understanding Sp1 PTMs advances our knowledge of cell signaling pathways in controlling Sp1 stability during cardiovascular disease onset and progression. It also aids in identifying novel pharmaceutical targets and biomarkers essential for preventing and managing cardiovascular diseases.